Synthesis and characterization of ketohydrazone ligands and its complexes with aluminium(Iii) and zinc(Ii) as potential emitting material in oled - Bahari, Haznita Rose (Universiti Teknologi Malaysia, 2005)
Ketohydrazone is a molecule that is able to act as a bidentate ligand through the O of C=O and N of N=C in the molecule. Three ketohydrazone ligands had been fully synthesized through the condensation reaction between 2-hydroxynaphthaldehydes with various hydrazine, salisylic hydrazide, benzyhydrazide and 2-furoic acid hydrazide in a 1:1 stoichiometry. The ligands had been characterized using infrared, 1HNMR and ultraviolet-visible spectrometer. Complexation reaction between all ligands and metal, with a stoichiometry of 1:2 for Zinc(II) : ligand and 1:3 for Aluminium(III) : ligand were carried out. All six complexes obtained were characterized using FTIR and UV-Vis spectrometer. The fluorescence properties of each ligands and complexes were investigated using luminescence spectrofluorometer at fluorescence emission wavelength at 406 nm and excitation wavelength at 470 nm. Results showed that all the ligands and molecules synthesized have the fluorescence properties and complexation with metal enhanced the intensity of the fluorescence. It was observed that complex of Al(NDB)3 showed the best potential as an emitting material for OLED as it has the highest fluorescence intensity compared to others.